Prospective, large‐scale multicenter trial for the use of drug‐coated balloons in coronary lesions: The DCB‐only All‐Comers Registry. Issue 2 (2nd October 2018) - Rosenberg, Mark; Waliszewski, Matthias; Chin, Kenneth; Ahmad, Wan Azman Wan; Caramanno, Giuseppe; Milazzo, Diego; Nuruddin, Amin Ariff; Liew, Houng Bang; Maskon, Oteh; Aubry, Pierre; Poyet, Raphael; Frey, Norbert
Abstract: Objectives: This prospective, observational all‐comers registry assessed the safety and efficacy of a Drug Coated Balloon‐only strategy (DCB‐only) in patients with coronary lesions. Background: Data regarding the performance of a DCB‐only approach, especially in patients with previously untreated de‐novo coronary artery disease (CAD), are still limited. Methods: This study was conducted as an international, multicenter registry primarily enrolling patients with de‐novo CAD. However, it was also possible to include patients with in‐stent restenosis (ISR). The primary endpoint was the rate of clinically driven target lesion revascularization (TLR) after 9 months. Results: A total of 1, 025 patients with a mean age of 64.0 ± 11.2 years were enrolled. The majority of treated lesions were de‐novo (66.9%), followed by drug‐eluting‐stent ISR (DES‐ISR; 22.6%) and bare‐metal‐stent ISR (BMS‐ISR; 10.5%). The TLR rate was lower in the de‐novo group (2.3%) when compared to BMS‐ (2.9%) and DES‐ISR (5.8%) ( P  = 0.049). Regarding MACE, there was a trend toward fewer events in the de‐novo group (5.6%) than in the BMS‐ (7.8%) and DES‐ISR cohort (9.6%) ( P  = 0.131). Subgroup analyses revealed that lesion type (95% CI 1.127–6.587); P  = 0.026) and additional stent implantation (95% CI 0.054–0.464; P  = 0.001) were associated with higher TLR rates. Conclusions: Our results show that DCB‐only angioplasty of de‐novo coronary lesions is associated with low MACE and TLR rates. Thus, DCBs appear to be an attractive alternative for the interventional, stentless treatment of suitable de‐novo coronary lesions.